Local conditions vs regional context: variation in composition of bird communities along the Middle Paraná River, an extensive river-floodplain system of South America - Lorenzón, Rodrigo Ezequiel (2016)
We studied spatial changes in species composition (i.e., beta diversity) of local assemblages of birds along 450 km of the Middle Paraná River, an extensive fluvial system of South America. Point counts were used to survey birds at 60 plots located in shrub swamps and marshes of the floodplain within four sites (15 plots per site). Two sites were surrounded by each of the two upland ecoregions. Beta diversity of bird assemblages was high and was more important than alpha diversity in shaping regional diversity (i.e., gamma diversity) of the fluvial system. Compositional changes were related to species turnover among plots, while nestedness dissimilarity was not important for shaping diversity patterns. Variation-partitioning analysis showed that local conditions (i.e., landscape composition within a radius of 200 m from the center of each plot) accounted for more spatial variation in assemblage composition than did location along the fluvial system. Adjacent upland ecoregions did not account for spatial changes in bird composition within the fluvial system. In conclusion, environmental heterogeneity created by flood pulses is an important factor for sustaining regional diversity of birds within the fluvial system through effects on beta diversity.